P1 of strawberry vein banding virus, a multilocalized protein, functions as a movement protein and interacts with the coat protein - Peng-huan RUI; Zhan-qi WANG; Wen-shu SHAN; Wei-wei XIA; Xiu-hong ZHOU; Lian-lian YANG; Lei JIANG; Tong JIANG (Journal of Integrative Agriculture, 2022)
Although the complete nucleotide sequence of strawberry vein banding virus (SVBV) has been determined and bioinformatic analysis has revealed that the SVBV genome could encode seven proteins, the precise function of each protein is unclear. This study provided evidence that the P1 protein of SVBV (SVBV-P1) possesses the following features. Bioinformatic and subcellular localization analyses showed that SVBV-P1 is localized in the cytoplasm and cell walls of epidermal cells in Nicotiana benthamiana, and it forms inclusion bodies associated with microtubules and the endoplasmic reticulum. Dilution experiments demonstrated that SVBV-P1 could move from the original agro-infiltrated cells to adjacent cells in N. benthamiana leaves. Further trans-complementation experiments demonstrated that SVBV-P1 could facilitate the intercellular movement of a movement-deficient potato virus X mutant in N. benthamiana leaves. Finally, yeast two-hybrid and bimolecular fluorescence complementation assays revealed that SVBV-P1 could interact with the SVBV coat protein, which is a major component of Caulimovirus virions. Results of the electrophoretic mobility shift assay indicated that SVBV-P1 lacks DNA-binding capability. In summary, the results suggest that SVBV-P1 is probably a movement protein of SVBV, providing new insights into the function of movement proteins of the Caulimovirus genus.